AN ANALYSIS OF FACTORS RELATED TO CONSUMER ACTIVE PARTICIPATION, BRAND ENGAGEMENT AND COMMUNITY TRUST IN ONLINE FOOD COMMUNITY PLATFORMS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose – With the growing importance of  consumer interaction on web and social media  platforms, consumer engagement has been  extensively examined for various brands but  not for online food community platforms. To  mitigate this gap in the literature, the current  study is undertaken to identify the factors that  impact the customer engagement model for an  online food community platform. The study also  discusses the drivers of the customer engagement  model and its outcomes for an online food  community platform. To investigate how well  these online food communities, engage with  customers, the study examines the constructs  i.e. community active participation, brand  engagement and community trust.  Design/methodology/approach – A  questionnaire-based survey is conducted with  the online food community members to gather  data. Exploratory factor analysis followed by  confirmatory factor analysis has been applied  to analyse the data. Findings – The study identifies the role and  significance of encouraging active participation  in engaging customers in an online food  community context. Further, it also recognizes  community trust to be a key factor in consumer  brand engagement. Research limitations/implications – The study  presents understanding to the marketers in terms  of managing customer engagement with their  online food communities.  Originality/value – There are numerous views  among researchers regarding the customer  engagement. Only limited studies have focussed  on this construct in the perspective of markets  in developing economies. No previous study is  done on studying customer engagement in an  online food community platform. Thus, the  study attempts to close this gap.
Keywords: Social networks; online food community platforms; consumer behaviour internet; active participation; brand engagement and community trust